Primjena vektoriranog potiska s osvrtom na superupravljivost istraživackog zrakoplova X-31A - Galović, Borivoj; Steiner, Sanja (Promet - Traffic&Transportation, 2012)
Vectored propulsion is a new concept of aircraft attitudecontrol by engines jet-deflection. Thrust vectoring researchhas become actualized during the last ten years, mainly formilitary application.The carried out experimental projects confirm the effectivenessof the thrust-vectoring systems in both conventionalaircraft attitude control and post-stall maneuverability enhancement.Apart from military aviation, the results of thrust-vectoringresearch are applicable in civil aviation, especially in STOLand VTOL aircraft design.